Language empowerment in the text of automotive product advertisements on print media in Padang City - Afrini Rahmi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This study against the backdrop of irregularities and problems use of advertising language. Irregularities and ambiguities of meaning will lead to wrong interpretation. This study aims to describe the disclosure of text messages advertising automotive products in the print media in the city of Padang in terms of the use of diction, style, and links the image with advertising messages. Data from the study found, the first proper diction with the concept of criteria, precise sense of value in the ad serves conative / directive / persuasive. Secondly, it was found 11 different style of language used in advertising. 11 kinds of style draws on the poetic function of language. Poetic function is intended effect of beauty in advertising. Third, the research found that images in advertising has three functions to reveal the message, namely as icons, indexes, and symbols